2017
DOI: 10.1098/rsif.2016.0889
|View full text |Cite
|
Sign up to set email alerts
|

A Lévy-flight diffusion model to predict transgenic pollen dispersal

Abstract: The containment of genetically modified (GM) pollen is an issue of significant concern for many countries. For crops that are bee-pollinated, model predictions of outcrossing rates depend on the movement hypothesis used for the pollinators. Previous work studying pollen spread by honeybees, the most important pollinator worldwide, was based on the assumption that honeybee movement can be well approximated by Brownian motion. A number of recent studies, however, suggest that pollinating insects such as bees per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…For instance, most of the transport of pollen between plants is carried out by wind or insect pollinators. This biological process is vital for the survival of the species, but it is also important for understanding transgenic pollen dispersal [13]. Of similar importance is the spreading of evolutionary novelties across populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, most of the transport of pollen between plants is carried out by wind or insect pollinators. This biological process is vital for the survival of the species, but it is also important for understanding transgenic pollen dispersal [13]. Of similar importance is the spreading of evolutionary novelties across populations.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of long-range dispersal effects, either as diffusive processes or by including long-range jumps, has been the topic of many researches [22,23,24,25,26,27,28,29]. Recently, Vallaeys et al [13] have stressed that the diffusive process "often seriously underestimates dispersal distances", and on the other hand, pure Lévy movements "often overestimates dispersal distances". Thus, methods that account for an equilibrated balance between diffusive and long-range dispersal are still needed for modeling epidemic processes in plants [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The black kite and the wolf trajectories appeared different from both Brownian and Lévy motions thus suggesting the possibility to study these movements using more complex behavioural models. Indeed, Brownian motion often underestimates long range movements while pure Lévy walk often overestimates them (Vallaeys, Tyson, Lane, Deleersnijder, & Hanert, 2017). More realistic motions might also be tested in the future (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent example is that of Chen et al [83], who showed from experiments that active transport within living cells described by time-dependent Brownian walks can self-organize into (truncated) Lévy walks. Other examples demonstrating this concept can be found elsewhere in the literature, e.g., swarming bacteria [84], pollen dispersal [85], etc. Despite this, from an ecological viewpoint, such as insect trapping, the motivation behind time-dependent diffusion, and how this is linked to the type of mechanisms involved, to date, has not been clearly understood [52].…”
Section: Discussionmentioning
confidence: 99%